PENGARUH HARGA, CITRA MEREK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MIE INSTAN PADA MAHASISWA AKTIF S1 AKUNTANSI UNIVERSITAS SYIAH KUALA - Fachhruddin, Rudy; Erlangga, Satria; mahdi, sayed (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This study aims to determine the effect of price, brand image and product quality on purchasing decisions of instant noodles on active undergraduate students of accounting at Syiah Kuala University by understanding how to make decisions. The research respondents were 85 people, namely active undergraduate accounting students at Syiah Kuala University. Data collection was carried out by distributing questionnaires directly to respondents in June to July 2021. This study used a simple random sampling method where the sample was taken randomly. The analytical method used is multiple linear regression with SPSS version 25 application. The results of the study prove that brand image and product quality have a significant positive effect on purchasing decisions for instant noodles in active undergraduate accounting students at Syiah Kuala University. Price has no effect on purchasing decisions for instant noodles for active undergraduate accounting students at Syiah Kuala University.